Comparing Digital Literacy Skills Gap Index: A Case from Pakistan and Indonesia - Muhammad Younus; Achmad Nurmandi; Dyah Mutiarin; Halimah Abdul Manaf; Andi Luhur Prianto; Imelda Zamjanah Rahmawati (Universitas Pendidikan Ganesha, 2024)
This paper thoroughly analyzes the computerized proficiency of two critical South Asian countries, Pakistan and Indonesia. This groundbreaking inquiry examines the rising importance of advanced education inside the worldwide circle, explaining the deterrents and conceivable outcomes these nations experience in an increasingly digitized society. This considers employment a thorough mixed-method approach to assess essential viewpoints of computerized proficiency competencies, enveloping mechanical availability, capability in computerized proficiency, and consolidating computerized instruments in instructive and word-related settings. Through a comparative examination of the investigative discoveries from Pakistan and Indonesia, the information for the comparative ponder is taken from the Wiley Computerized Aptitudes Crevice File site. The results of our study propose that Pakistan and Indonesia significantly impede computerized proficiency. In any case, it is fundamental to note that there are recognizable contrasts within the characteristics and greatness of these incongruities. Pakistan must illustrate a more pronounced division characterized by errors within the accessibility of computerized assets and conceivable outcomes for preparing. In differentiation, Indonesia is hooked on challenges concerning advanced substances and the genuineness of the data. Also, it gives commonsense proposals for policymakers, teachers, and partners in nations like Pakistan, Indonesia, and other creating economies working towards leveraging the openings displayed by the advanced times.